Analysis of the Health Care Labor Market in Peru - Jimenez, Michelle; Mantilla, Eduardo; Huayanay, Carlos; Mego, Michael; Vermeersch, Christel (World Bank, Washington, DC, 2015)
This report aims to provide an updated analysis of labor market trends for the health workforce in Peru, focusing on the basic health team, physician, nurse, and midwife, and other health professionals related to current priorities. Peru has been labeled as a country with a shortage of health professionals (that is, with less than 25 professionals per 10,000 inhabitants), and although the most recent numbers indicate that the situation has improved, the shortages are bound to become more acute as the country aims to achieve Universal Health Coverage. The authors found that the country trains both in public and private universities a large number of professionals, but that the majority of trained professionals do not then go on to work for the public sector. This dynamic had not been described before and challenges current assumptions of human resources needs and availability. There is very little reliable data on numbers, type and work conditions for human resources working outside the public sector, including the social security insurance health system (EsSalud), other health insurance providers, and the private sector, and as a result no detailed information can be obtained about the distribution of health professionals outside the public sector. For policy purposes, it is necessary to improve the quality and integration of HRH information across the sector.